2010
DOI: 10.1161/hypertensionaha.109.145490
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics in Angiotensin II-Induced Cardiac Hypertrophy

Abstract: Abstract-Angiotensin II (Ang II) induces mitochondrial dysfunction. We tested whether Ang II alters the "metabolomic"profile. We harvested hearts from 8-week-old double transgenic rats harboring human renin and angiotensinogen genes (dTGRs) and controls (Sprague-Dawley), all with or without Ang II type 1 receptor (valsartan) blockade. We used gas chromatography coupled with time-of-flight mass spectrometry to detect 247 intermediary metabolites. We used a partial least-squares discriminate analysis and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…The effect of angiotensin II-induced mitochondrial dysfunction and subsequent cardiac hypertrophy in the rat has been investigated by GCxGC-TOF MS. 54 A wide range of metabolic changes were identified in a transgenic model of angiotensin stimulation (where rats had both human renin and angiotensinogen genes), including an increase in hypoxanthine consistent with purine degradation compared with the wild-type strain, as measured by GC-MS.…”
Section: Metabolomics In Cardiologymentioning
confidence: 99%
“…The effect of angiotensin II-induced mitochondrial dysfunction and subsequent cardiac hypertrophy in the rat has been investigated by GCxGC-TOF MS. 54 A wide range of metabolic changes were identified in a transgenic model of angiotensin stimulation (where rats had both human renin and angiotensinogen genes), including an increase in hypoxanthine consistent with purine degradation compared with the wild-type strain, as measured by GC-MS.…”
Section: Metabolomics In Cardiologymentioning
confidence: 99%
“…Each lane corresponded to one rat and all 4 groups were run on one gel. SIRT1 immunoblotting was performed from nuclear proteins isolated as described elsewhere 12 . OPA1 immunoblotting was performed from mitochondrial proteins.…”
Section: Proteome Analysis Of Isolated Mitochondriamentioning
confidence: 99%
“…Ang II-induced amplification of mitochondrial ROS activates several downstream redox-sensitive signal transduction pathways implicated in cardiac hypertrophy and apoptosis, including p38 mitogen-activated protein kinase, nuclear factor " light chain enhancer" of activated B cells, and calcineurin nuclear factor of activated T cells. 11 We showed recently that Ang II-induced cardiac hypertrophy is associated with mito-chondrial dysfunction, distinct cardiac substrate use, 12 and downregulation of several genes encoding mitochondrial respiratory chain and lipid metabolism. 13 Caloric restriction (CR) extends life span and reduces the incidence of diabetes mellitus, cancer, brain atrophy, and cardiovascular diseases.…”
mentioning
confidence: 99%
“…In a separate study, we very recently observed distinct patterns of cardiac substrate utilization and mitochondrial dysfunction in dTGRs. 27 Recently, Koudouna et al 28 showed that levosimendan improved the initial outcome of cardiopulmonary resuscitation in an experimental model of cardiac arrest. We found that lifelong levosimendan treatment was associated with a 58% increase in mean survival time and a 27% increase in median survival time.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Cardiac mRNA expression analysis by quantitative real-time reverse transcriptase-PCR Quantitative real-time reverse transcriptase-PCR was performed using the LightCycler instrument (Roche Diagnostics, Neuilly sur Seine, France) for detection of atrial natriuretic peptide (ANP), SERCA2, NCX-1, a-MHC, b-MHC, MCP-1, Bax, PGC-1a and ribosomal 18S mRNA as described elsewhere. 18,27 Briefly, total RNA from the rat hearts were collected using Trizol (Gibco, Invitrogen, Carlsbad, CA, USA), treated with DNAse 1 (deoxyribonuclease 1, Sigma Chemicals, St Louis, MO, USA) and reverse transcribed to cDNA by reverse transcription enzyme (Im-Prom-II reverse transcription system, Promega, Madison, WI, USA). A volume of 1 ml of cDNA was subjected to quantitative real-time PCR for detection of ANP, a-MHC, b-MHC, MCP-1, Bax, PGC-1a and ribosomal 18S mRNA.…”
Section: Tissue Morphology and Cardiomyocyte Cross-sectional Areamentioning
confidence: 99%